Improvised Explosive Device Blast Injuries to the Craniofacial Region: Wound Characteristics and Management. Issue 5 (July 2020) - Arya, Saurabh; Jose, Anson; Rawat, Aditi
Abstract : Abstract: Improvised explosive device blast injuries frequently report at our center and showed the maximum amount of contamination and damage, both in the facial soft tissues and the skeletal tissues with impregnation of splinters with size ranging from 2 mm to 10 mm. Should splinters be always explored is questionable and varies with every case. The reconstruction in such cases was done with titanium mini-plates along with extensive use of local vascular flaps for soft tissue repair in majority of the cases. Soldier who sustained splinter injuries wrt orbital floor were managed with splinter exploration using C-arm and orbital floor reconstruction using titanium mesh. Abstract : Supplemental Digital Content is available in the text